ROLE OF ARTIFICIAL INTELLIGENCE IN MODERN LIBRARIES - Laxmanra, Phugnar Prashant (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The integration of Artificial Intelligence (AI) in modern libraries is revolutionizing information management, user services, and operational efficiency. This study explores the multifaceted role of AI technologies such as machine learning, natural language processing, and robotics in enhancing library functions, including cataloging, reference services, user interaction, and digital resource management. It assesses the benefits, challenges, and evolving trends in AI adoption, highlighting how AI-driven tools contribute to personalized experiences, automated workflows, and improved accessibility. The paper also discusses ethical concerns and future prospects, emphasizing the strategic importance of AI for library transformation in the digital age.